2014
DOI: 10.1590/s0104-77602014000100015
|View full text |Cite
|
Sign up to set email alerts
|

Viabilidade econômica e rotação florestal de plantios de candeia (Eremanthus erythropappus), em condições de risco

Abstract: *Autor para correspondência: donizete@dcf.ufla.br RESUMO: Objetivou-se neste estudo analisar a viabilidade econômica e determinar a rotação econômica de plantios de candeia em diversos espaçamentos, em condições de risco. O estudo foi realizado a partir de um experimento de plantio de candeia constituído de quatro espaçamentos (1,5 x 1,5 m; 1,5 x 2,0 m; 1,5 x 2,5 m e 1,5 x 3,0 m), para os quais se obtiveram os fluxos de caixa relacionados às diversas idades de corte. Para a análise de risco utilizou-se o métod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
7
0
4
Order By: Relevance
“…Several studies have already been published regarding the sustainability of plantations for oil extraction from E. erythropappus (Feitosa et al, 2009;Silva et al, 2014;Scolforo et al, 2016a, b). Practically, plantations of E. erythropappus in the coming decades may be most feasible in the western parts of the Canastra mountain ranges, where we predicted some potential gains in suitable habitat for the species.…”
Section: Currentmentioning
confidence: 99%
“…Several studies have already been published regarding the sustainability of plantations for oil extraction from E. erythropappus (Feitosa et al, 2009;Silva et al, 2014;Scolforo et al, 2016a, b). Practically, plantations of E. erythropappus in the coming decades may be most feasible in the western parts of the Canastra mountain ranges, where we predicted some potential gains in suitable habitat for the species.…”
Section: Currentmentioning
confidence: 99%
“…While for Pinus radiata in Chile the negative NPV value had 50% probability of occurrence due to the low productivity of the sites (Carmona;Aranda, 2003). For Candeia (Eremanthus erythropapus) plantations in Brazil the risk of negative values was 9.1% (Silva et al, 2014). Our study showed lower returns for the combination between regime A and site 17 (Table 4) and, even in this less favorable situation, the probability of occurrence of negative values was around 0.4%.…”
Section: Risk Analysesmentioning
confidence: 55%
“…Inicialmente, constata-se que os custos totais com a implantação e manutenções aumentaram com a densidade do povoamento. Este resultado coincide com o encontrado por outros autores, que observaram que os custos de implantação, manutenção e exploração aumentam com a densidade do povoamento, devido, principalmente, à maior demanda por insumos e mão de obra (PAULINO, 2012;SILVA et al, 2014;SILVEIRA, 2014 1 Valores em dólar, sendo US$1,00 = R$3,00 (mai/2015).…”
Section: Resultsunclassified
“…Na escolha do espaçamento deve-se buscar fornecer, a cada planta, espaço adequado para que ela expresse o máximo crescimento, potencializando a qualidade da madeira e reduzindo os custos da operação (SILVA et al, 2010). Sendo necessário considerar vários fatores como o uso final da madeira, qualidade do local de plantio, equipamentos que serão utilizados durante o ciclo da floresta, dentre outros (PAULINO, 2012).…”
Section: Período 2006-2012 (Associação Brasileira De Produtores De Flunclassified